Raising the bar (23). Issue 1 (2nd January 2023) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Bond-Smith, Steven; Chasco, Coro; Corrado, Luisa; Ditzen, Jan; Felsenstein, Daniel; Fuerst, Franz; Monastiriotis, Vassilis; Quatraro, Francesco; et al.
ABSTRACT: This editorial summarizes the papers in issue 18(1) (2023). The first paper sets out a game-theoretic duopolistic spatial model to investigate whether online retailing causes more transportation-related emissions than offline retailing. The second paper proposes a methodology for statistically downscaling projected gross domestic product (GDP). The third paper presents a Bayesian approach for the estimation of a spatial weight matrix. The fourth paper proposes a two-step spatial non-parametric estimator for the distribution dynamics approach to study income convergence, extended with spatially dependent error terms. The fifth paper combines a gravity-RAS approach with the estimation of an econometric gravity model when regional export and import totals are available but interregional trade data are not. The sixth paper estimates the impact of country-specific immigrants settled in 611 Italian regions on the arrival of new immigrants in destination and adjacent regions. The seventh paper investigates the impact of the market potential of a region on individual wages. The eighth paper tests whether female labour force participation rates vary with past participation rates in their own and neighbouring counties.